1987
DOI: 10.1002/ana.410220607
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in isolated noncompressive spinal cord syndromes

Abstract: The frequency with which patients presenting with acute or chronic noncompressive cord syndromes subsequently develop multiple sclerosis is uncertain. Magnetic resonance imaging (MRI) was performed on 121 patients with such syndromes to determine the frequency of asymptomatic brain lesions and to assess the sensitivity of MRI in detecting the local cord lesion. MRI findings were compared with those from visual, brainstem, and somatosensory evoked potentials (VEPs, BAEPs, SEPs), and cerebrospinal fluid electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
7

Year Published

1988
1988
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(35 citation statements)
references
References 20 publications
2
26
0
7
Order By: Relevance
“…Using the 2005 diagnostic criteria for MS , 10% to 15% of CIS patients will convert to definite MS based on MRI changes alone without having any clinical episodes for up to two decades (Chard et al, 2011). Nevertheless, T2 abnormalities are present in 50-70% of patients at the CIS stage (Miller et al, 1987;Beck et al, 1993a;Sastre-Garriga et al, 2003). In addition, the typical MRI findings correspond to the known histopathology of the disease.…”
Section: Prognosismentioning
confidence: 95%
“…Using the 2005 diagnostic criteria for MS , 10% to 15% of CIS patients will convert to definite MS based on MRI changes alone without having any clinical episodes for up to two decades (Chard et al, 2011). Nevertheless, T2 abnormalities are present in 50-70% of patients at the CIS stage (Miller et al, 1987;Beck et al, 1993a;Sastre-Garriga et al, 2003). In addition, the typical MRI findings correspond to the known histopathology of the disease.…”
Section: Prognosismentioning
confidence: 95%
“…[3][4][5] Thus, approximately 50 to 80% of individuals who present with a clinically isolated syndrome (CIS) already have lesions on MRI, consistent with prior (occult) disease activity. [6][7][8][9][10][11][12][13] Two randomized, controlled trials of interferon beta (IFN␤) have recently demonstrated a treatment benefit in patients with a CIS and MRI abnormalities suggestive of MS. 14,15 All existing diagnostic criteria for RRMS, including those of Schumacher et al 16 and Poser et al 17 as well as a recent consensus statement, 18 require two or more distinct events separated in time (generally by more than a month) in addition to involvement of at least two distinct areas of the CNS (the so-called criteria of dissemination in time and space). Importantly, also, all of the existing diagnostic schemes require the exclusion of alternative diagnoses by appropriate laboratory and radiographic studies prior to the application of the diagnostic algorithm.…”
Section: Neurology 2003;61:602-611mentioning
confidence: 99%
“…The lesions responsible for spinal or optic nerve demyelination can also be imaged in vivo (Miller et al, 1987(Miller et al, ,1988. Correlations between magnetic resonance images, the evolution of symptoms, and clinical neurophysiology show that the deficits, at least in optic neuritis, are associated with altered blood-brain barrier permeability and conduction block, without demyelination or axonal degeneration necessarily having occurred (Youl et al, 1991).…”
Section: Imagingmentioning
confidence: 99%